PENGEMBANGAN SISTEM PEMBAYARAN UNTUK DESA WISATA TRI EKA BUANA DENGAN ONLINE PAYMENT - Sudhana, I G P Fajar Pranadi; Sadguna, I Gde Agus Jaya; Waisnawa, I Gede Nyoman Suta; Yulianthi, Ayu Dwi; Harmini, A A Ayu Ngurah (Dharma: Jurnal Pengabdian Masyarakat, 2021)
Since 2019, Tri Eka Buana Village, located in Sidemen sub-district, Karangasem Bali Regency, through the Bali State Polytechnic service team has received a PPDM grant to form a tourism village with natural potential and a producer of traditional Balinese arak drinks. Various kinds of activities from the solutions offered have been implemented in the first year of 2019. including compiling a master plan for developing a tourism village, formulating a village cleanliness supervision system, carrying out socialization of tourism village spatial planning, socialization and tourism outreach, and compiling a tourism village marketing program through digital marketing . One of the activities that has been carried out is the development of the Tri Eka Buana Tourism Village website. Online transactions are increasingly in demand, even have become a trend among the wider community. Besides, it can be done anytime and anywhere without any time or distance restrictions. E-payment offers various kinds of convenience and practicality in making payments. Various kinds of payment methods can be integrated into the system making it easier for customers to make payments according to orders made. The tourism village of Tri Eka Buana Sidemen Karangasem Bali, can take advantage of this online payment system to help tourism village operations in the future. The development of this online payment system can be developed by building a tourism village website, adding ecommerce facilities to the website that has been built, registering and activating one of the payment gateway services, and integrating the Tri Eka Buana tourism village website with a payment gateway service.